Game anim video game animation explained - Cooper, Jonathan (Animator) (CRC Press, Taylor and Francis Group, 2019)
"Hints, tips, and best practices for creating video game animation learned from some of the largest and most successful video game productions in the world. This book de-mystifies the animation side of game development, explaining every step of the process while providing valuable insights and work philosophies for creating the best animation for beginners and professionals. Taking readers through a complete game project and featuring workable examples and interactive tutorial scenes, this book provides clear understanding of game animation fundamentals and explanations of the very latest in cutting edge technology and techniques to provide a holistic approach to the field of game animation"-- Provided by publisher.